2023
DOI: 10.17645/mac.v11i1.6004
|View full text |Cite
|
Sign up to set email alerts
|

Level Playing Field or Politics as Usual? Equalization–Normalization in Direct Democratic Online Campaigns

Abstract: Are digital technologies leveling the playing field or reinforcing existing power relations and structures? This question lies at the core of the equalization vs. normalization debate. The equalization thesis states that the affordances of digital technologies help less-powerful political actors to compete with their more resource-rich counterparts, thereby overcoming structural disadvantages inherent to the political landscape. The normalization thesis, in contrast, suggests that more powerful and resource-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Analyzing Facebook posts by campaign actors and user reactions to these posts before 91 votes in Switzerland from 2010 to 2020, Fischer and Gilardi (2023) found that the amount of Facebook activities before referendum campaigns increases over time. Strikingly, users engage with campaigns of the challenger camp about as much as with those of pro-government campaigns.…”
Section: Current Perspectives On Referendum Campaignsmentioning
confidence: 99%
“…Analyzing Facebook posts by campaign actors and user reactions to these posts before 91 votes in Switzerland from 2010 to 2020, Fischer and Gilardi (2023) found that the amount of Facebook activities before referendum campaigns increases over time. Strikingly, users engage with campaigns of the challenger camp about as much as with those of pro-government campaigns.…”
Section: Current Perspectives On Referendum Campaignsmentioning
confidence: 99%